The Effect of Financial Ratio on Profit Growth in Infrastructure Sector Companies Listed on the Indonesia Stock Exchange - Rifa Alfiandi; Ni Luh Supadmi (International Journal of Economics, Commerce, and Management, 2025)
Profit growth is the rate of increase in profit obtained by a company. Profit growth is an important factor in assessing a company's financial performance. This study aims to examine the effect of financial ratios on profit growth in infrastructure sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2019-2022. The research sample used was 20 companies with 80 observation samples. The financial ratios used are liquidity, solvency, profitability, and activity ratios. These financial ratios are proxied by the Current Ratio (CR), Debt to Equity Ratio (DER), Return on Assets (ROA), and Total Asset Turnover (TAT), respectively. Testing was carried out using multiple linear regression analysis. Based on the results of the hypothesis test, it is known that the profitability ratio proxied by Return on Assets (ROA) has a positive effect on profit growth and the activity ratio proxied by Total Asset Turnover (TAT) has a negative effect on profit growth. Other results, namely the liquidity ratio proxied by the Current Ratio (CR) and the solvency ratio proxied by the Debt to Equity Ratio (DER) have no effect on profit growth. These results mean that the profitability ratio and activity ratio can be determinants of profit growth predictors and can be a reference for investors to make investment decisions.